Association between daily life experience and psychological well-being in people living with nonpsychotic mental disorders: Protocol for a systematic review and meta-analysis. Issue 4 (January 2018) - Ho, Jeffery; Ngai, Shirley P.C.; Wu, William K.K.; Hou, Wai Kai
Abstract: Background: Evidence has shown that people living with nonpsychotic mental disorders experience difficulties in maintaining their daily living, consequently impacting on psychological well-being. However, the role of daily life experience remains unclear. This systematic review and meta-analysis aims to determine the association between daily life experience and psychological well-being in people living with nonpsychotic mental disorders, and evaluate daily life experience as a moderator of psychological well-being in this population. Methods: Literature search will be performed using a combination of title/abstract words and subject headings on 7 electronic databases according to predefined inclusion and exclusion criteria. Data will be extracted by 4 independent reviewers (JH, SPCN, WKKW, and WKH). Disagreement will be resolved by discussion with senior reviewers. Observational studies involving subjects with unipolar depression, bipolar disorder, anxiety disorder, acute stress disorder, as post-traumatic stress disorder as distinct groups with quantitative measurement of daily life experience and psychological well-being will be included. Results: Effect sizes will be pooled by random effects model. The quality of the studies will be assessed using Newcastle–Ottawa scale. Heterogeneity between studies will be quantified using I 2 index. This review is registered in PROSPERO. Conclusions: While symptoms and existing treatments of nonpsychotic mental disorders could be long term and dependent upon medical regimens, sustaining daily life experience will be a potentially important and concrete pathway that empowers patients to recover from the disorders, maintain or enhance psychological well-being, and be reintegrated into society. Findings of this review will inform prospective interventional trials of enhancing daily life experience in prevention of recurrence and enhancing psychological well-being in people living with nonpsychotic mental disorders.